ANALYSIS ON MAGNETO-AEROELASTIC TRANSVERSE VIBRATION OF ROTATING CONDUCTIVE CIRCULAR PLATE - HU YuDa; LI WenQiang (Jixie qiangdu)
Based on the Kirchoff plate theory and Hamiltonian principle,the magneto-aeroelastic transverse vibration equations of rotating conductive circular plate were derived. According to principles of electromagnetic field combined with a simplified aerodynamic model,the expressions of electromagnetic force and aerodynamic load of rotating circular plate were given.The magneto-aeroelastic free differential equation of conductive rotating circular plate was presented by means of Galerkin method. The curves of natural vibration characteristics of circular plates with two boundary conditions were drawn respectively.The analysis on the law of the vibration natural frequency varying with magnetic flux density,plate thickness,aerodynamic load and rotation speed is presented. The relationship graphs of magnetic flux density varying with plate thickness,aerodynamic load and rotation speed are described in the critical damping case.